Grey Zones in the Diagnosis of Adult Migraine without Aura Based on the International Classification of Headache Disorders-Iii Beta: Exploring the Covariates of Possible Migraine without Aura - Aynur Ozge; Elif Aydinlar; Bahar Tasdelen (Pain Research and Management)
BACKGROUND: Exploring clinical characteristics and migraine covariates may be useful in the diagnosis of migraine without aura.